Tai chi for treating osteopenia and primary osteoporosis: a meta-analysis and trial sequential analysis - Zhang YL (Dove Medical Press, 2019)
Yili Zhang,1,2 Yan Chai,3 Xiaojie Pan,4 Hao Shen,1 Xu Wei,5 Yanming Xie1 1Institute of Basic Research in Clinical Medicine, China Academy of Chinese Medical Sciences, Beijing, China; 2School of Traditional Chinese Medicine, Beijing University of Chinese Medicine, Beijing, China; 3Department of Epidemiology, University of California, Los Angeles, CA, USA; 4Department of Human Nutrition and Health, Wageningen University and Health, Wageningen, The Netherlands; 5Department of Scientific Research, Wangjing Hospital, China Academy of Chinese Medical Sciences, Beijing, China Purpose: The aim of this meta-analysis was to evaluate the efficacy of Tai chi (TC) as an adjuvant treatment for osteopenia and primary osteoporosis. Methods: We went through eight databases to identify relevant randomized controlled trials that compared TC with a control group. The primary outcome was osteoporosis-related fractures (fracture incidence). Meta-analyses and trial sequential analyses (TSA) were conducted using RevMan 5.3 and TSA 0.9. Results: Fifteen randomized controlled trials involving a total of 857 patients were included in the analyses. No trials reported primary outcome; however, bone mineral density (BMD) values differed significantly in subgroup 1 (TC vs no treatment; weighted mean difference [WMD] =0.05 g/cm2, 95% CI 0.03 to 0.07; P<0.00001; P for heterogeneity =0.22, I2=22%) and subgroup 2 (TC vs conventional treatments; WMD =0.16 g/cm2, 95% CI 0.11 to 0.21; P<0.00001; P for heterogeneity =0.008, I2=75%). In addition, two trials compared TC with conventional treatments, which found a significant difference in bone gla protein (standardized mean difference =-1.18, 95% CI −1.66 to −0.70; P<0.00001; P for heterogeneity =0.58, I2=75%). The results of the BMD were confirmed by TSA. Also, TC may have a certain effect on the relief of osteoporotic pain (WMD = −2.61, 95% CI -3.51 to −1.71; WMD = −1.39, 95% CI −2.01 to −0.77). However, it did not promote the quality of life, level of serum calcium, serum phosphorus, and also had no effect on bone turnover markers. Conclusion: Although there is no study monitoring fracture incidence, TC may be beneficial for patients in improving BMD values, level of bone gla protein, and relieving osteoporotic pain. However, due to the low methodological quality, current evidence for treating osteopenia and primary osteoporosis through TC is insufficient. Keywords: Tai chi, osteopenia, primary osteoporosis, evidence based medicine, trial sequential analyses